2006
DOI: 10.3354/meps308017
|View full text |Cite
|
Sign up to set email alerts
|

Larval dispersal reveals regional sources and sinks in the Great Barrier Reef

Abstract: We analysed simulated connectivity patterns for reef fish larvae in the Cairns section of the Great Barrier Reef, and identified 2 key subregions that exhibit regional scale source-sink dynamics. The source and sink were separated latitudinally by a boundary at 16.1°S, with the source subregion lying to the north. Larval transport between the 2 subregions was predominantly unidirectional, from north to south. Only a few local populations, described here as 'gateway reefs', were able to transport larvae from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(124 citation statements)
references
References 25 publications
4
120
0
Order By: Relevance
“…3 and Methods). Theoretically, at some extremely high level of density dependence, spatial heterogeneity in larval connectivity, which creates differences in the importance of subpopulations, will diminish (40). We tested the effect of different levels of larval density dependence by altering demographic parameters (Methods) and found that the robustness of metapopulations to subpopulation removal was indeed affected by these changes; removal curves were steeper at lower compensation ratios (CRs) and less intense larval density dependence (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3 and Methods). Theoretically, at some extremely high level of density dependence, spatial heterogeneity in larval connectivity, which creates differences in the importance of subpopulations, will diminish (40). We tested the effect of different levels of larval density dependence by altering demographic parameters (Methods) and found that the robustness of metapopulations to subpopulation removal was indeed affected by these changes; removal curves were steeper at lower compensation ratios (CRs) and less intense larval density dependence (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Often dispersal is thought of as having a smoothing effect-reducing spatial heterogeneity and thereby lowering the potential gains from high-resolution policy prescriptions. However, when dispersal is asymmetric, spatial ecological heterogeneity can be exacerbated rather than reduced [5,23,24]. Moreover, dispersal between different locations can create additional management complexities.…”
Section: Introductionmentioning
confidence: 99%
“…Here we consider one of the simplest and most used, the Beverton-Holt model (Beverton and Holt, 1957), slightly modified as proposed in Hassell (1975) to account for demographic fluctuations. This model was originally formalized to describe the dynamics of fish stocks and has already been used to link larval dispersal to recruitment dynamics in sessile aquatic population with a benthonic life stage (e.g., James et al, 2002;Armsworth, 2002;Bode et al, 2006). In the modified Beverton-Holt model, larval survival is supposed to decrease with the abundance of settling larvae itself due to competition for limited resources (either nutrients or space, or both).…”
Section: The Species Life Cyclementioning
confidence: 99%
“…Larval transport by the water flow is modeled by a Lagrangian approach, which represents a common choice in the literature (e.g., Siegel et al, 2003; see also Werner et al, 2007;Cowen and Sponaugle, 2009 and more references therein), since it provides a natural and accurate framework to describe larval movement. In our simple approach, we consider that dispersing larvae are passively transported by currents, i.e., that they are unable to swim, orient themselves or perform vertical migrations, apart from the capability to settle at the bottom of the water body in the location where they reach maturity (e.g., Bode et al, 2006). Although the assumption of passive transport is quite common in the description of larval dispersal (e.g., James et al, 2002;Aiken et al, 2007), it should be noted that active movements can also play a remarkable role in determining the mean distance traveled by larvae (Steneck, 2006;Cowen et al, 2006;Paris et al, 2007;Werner et al, 2007;Cowen and Sponaugle, 2009).…”
Section: The Larval Transport Modelmentioning
confidence: 99%
See 1 more Smart Citation